Human activity-driven self-powered hair follicle stimulation system. (1st December 2022) - Heo, Deokjae; Jung, Sungwon; Kim, Jungbum; Yong, Hyungseok; Park, Sohyeon; Kim, Dongchang; Cho, Seoungeun; Cha, Kyunghwan; Ryu, Hanwook; Jin, Youngho; Lee, Wonhwa; Lee, Sangmin; et al.
Abstract: Alopecia is one of the most common and distressing diseases that can remain traumatic for an individual. Various pharmacological and non-pharmacological treatments for alopecia have been developed; however, critical side effects ( e.g., impotence) or limitations in terms of hair regeneration potential still exists. One of the non-pharmacological treatments, physical stimulation, has been proven effective for hair regeneration; however, the resultant discomfort and the need for external components such as power supply remain problems in its widespread use. Here, we introduce an innovative human activity-driven internal hair follicle stimulation system (HIFS) that utilizes alternating current (AC) electric energy abandoned during human activities to internally stimulate hair follicles and tissues through the human body. The internal electric field concentration by simply applying conductive gel HIFS and cap-type/hairpin-type HIFS was investigated via 3D electrostatic simulation and actual electrical measurement experiments. The internally concentrated electric field could significantly increase the secretion of hair regeneration-associated growth factors in the tissues and the number of hair follicles in hair-less mice without any side effects. Graphical Abstract: ga1 Highlights: First study to report on a novel mechanism that can treat alopecia via body-mediated electric potential transfer and electric field concentration Quantitative electrical output analysis according to various daily scenarios and design parameters for effective HIFS application Successful demonstration of effects of the HIFS on the increase of hair follicle numbers and hair regeneration via in vitro/vivo